Creation and tidal advection of a cold salinity front in Storfjorden: 2. Supercooling induced by turbulent mixing of cold water. Issue 8 (1st August 2013) - McPhee, Miles G.; Skogseth, Ragnheid; Nilsen, Frank; Smedsrud, Lars H.
Abstract : [1] Measurements near the edge of fast ice in Freemansundet, Svalbard, reveal mixing processes associated with tidal advection of a sharp front in salinity, including possible supercooling induced by double diffusion in a fully turbulent water column. The front translated back and forth with the semidiurnal tide between an area of mobile (drifting) ice in Storfjorden proper, and the narrow sound covered by fast ice. Water on each side of the front was near its salinity‐determined freezing temperature. Instruments deployed about 400 m into the sound from the fast ice edge measured current, temperature, conductivity, and turbulence quantities through several tidal cycles. Turbulence data illustrate that as the steep horizontal salinity (density) gradient advected past the measurement site, vertical shear near the fast‐ice base induced marked flood/ebb asymmetry in turbulent mixing. As fresher water entered the sound on the flood phase, inward transport of denser water near the upper boundary was retarded, leading to statically unstable conditions and enhanced turbulence. The opposite occurred during ebb tide, as denser water underran lighter. Transient episodes of supercooling accompanied frontal passage on both flood and ebb phases. The most likely explanation for a zone of supercooled water within the strongly mixed frontal region is that during mixing of fresher, slightly warmer (but still at freezing) water from outside with saltier, colder water in the sound, the former constituent lost heat faster than gaining salt. This interpretation (differing turbulent diffusivities for heat and salt) challenges strict application of Reynolds analogy for highly turbulent shear flow. Key Points: Under‐ice boundary layer processes in tidal regime with rapid salinity changes Near boundary turbulence in a sheared, horizontal salinity (density) gradient Supercooling by double diffusive mixing of different water masses near freezing